The Effect of Providing Education on Improving Toddler Nutrition on Maternal Knowledge in the Teriak Health Center, West Kalimantan - Fajrin, Dessy Hidayati; Neliati, Uwet (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
Nutritional status is a measurement of the amount of nutrient intake and utilization by the body. Nutritional status is assessed through anthropometric measurements of body weight index according to age. The factors that cause malnutrition are; infectious diseases, environmental sanitation hygiene, inadequate health services, maternal education, maternal employment. To determine the knowledge of mothers before and after being given education about improving nutrition for toddlers at the Teriak Health Center working area, Bengkayang Regency. This study uses a quasy experiment design with a pre test and post test without control approach. The research was conducted from May 5 to 13, 2023 using a questionnaire. The population of this study were mothers who had undernourished children at the Teriak Health Center. This study used a purposive sampling technique with 37 respondents. The analysis used is the paired Shapiro-Wilk test. The results showed that before being given knowledge, the average obtained was 6.57 and after being given knowledge, the average obtained was 8.19. This means that there was a difference in the level of knowledge of mothers before and after being given nutrition education with a value of p = 0.000 (p <0.05). There is a difference in the level of knowledge of mothers about nutrition before and after being given education about nutrition at the Teriak Health Center, Bengkayang Regency.